2007
DOI: 10.1111/j.1574-6968.2006.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

First description of nonmotileVibrio vulnificusstrains virulent for eels

Abstract: Nonmotile Vibrio vulnificus strains were isolated as pure cultures from body ulcers and internal organs of wild diseased European eels caught in a Mediterranean freshwater coastal lagoon. All 54 V. vulnificus isolates were nonmotile, indole-, ornithine decarboxilase-, mannitol- and cellobiose-positive, developed the opaque variant in culture, belonged to the O-antigenic serovar A and were highly virulent for eels by both intraperitoneal injection and immersion challenges. The nonmotile phenotype found in our V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Second, the historical series of edwardsiellosis at the L′Albufera Lake (2003, 2004, 2005, 2008 and 2014 surveys), with total prevalence values ranging from 5%-11.8% (Esteve & Alcaide, 2009;Esteve et al, 2017; present study), better indicated that edwardsiellosis could be a native bacterial disease. However, neither this long incidence period nor the prevalence values observed fit with the "outbreak" concept, in contrast to that observed for other bacterial diseases (Esteve et al, 2007(Esteve et al, , 2017.…”
Section: L′albufera′s Eel Fisherycontrasting
confidence: 93%
“…Second, the historical series of edwardsiellosis at the L′Albufera Lake (2003, 2004, 2005, 2008 and 2014 surveys), with total prevalence values ranging from 5%-11.8% (Esteve & Alcaide, 2009;Esteve et al, 2017; present study), better indicated that edwardsiellosis could be a native bacterial disease. However, neither this long incidence period nor the prevalence values observed fit with the "outbreak" concept, in contrast to that observed for other bacterial diseases (Esteve et al, 2007(Esteve et al, , 2017.…”
Section: L′albufera′s Eel Fisherycontrasting
confidence: 93%
“…The only exception was the motility characteristic, which was negative for two isolates from wild eels. The lack of motility has already been reported in other typically motile bacterial pathogens (Fouz et al, 2006b;Gardel & Mekalanos, 1996), including V. vulnificus (Esteve et al, 2007). The use of vaccination against V. vulnificus at farms (Esteve-Gassent et al, 2004) could have favoured the emergence of these non-motile strains by selective pressure against flagellar antigens, similarly to what has occurred with other motile fish pathogens (Fouz et al, 2006b).…”
Section: Discussionmentioning
confidence: 84%
“…Biotype 1 is ornithine decarboxylase-and indole-positive, biotype 2 is orni-thine decarboxylase-and indole-negative, and biotype 3 is cellobiose-negative (Tison et al 1982, Bisharat et al 1999, Warner and Olivier 2008. In addition, Esteve et al (2007) described wild-type V. vulnificus biotype 2, serovar A strains, which were non-motile due to the lack of a sheathed polar flagellum. The literature indicates that three biotypes are potentially pathogenic for humans (Baker-Austin et al 2018).…”
Section: Discussionmentioning
confidence: 99%